Pengembangan Lembar Kerja Peserta Didik Berkarakteristik Project Based Learning pada Mata Pelajaran IPAS Kelas IV SD Negeri 30 Pontianak Utara - Indah Nur Rahmah; Kartono Kartono; Bistari Bistari (Journal on Education, 2024)
This research aims to produce a product, namely a student worksheet with project based learning characteristics in the science and science subject class IV at SD N 30 North Pontianak that is valid and suitable for use. The research method used is research and development (Research & Development) Thiagarajan 4D model (define, design, development and disseminate). The data source for this research is the validation results of two validator experts and a questionnaire of student responses after using the product that has been developed, namely student worksheets with project based learning characteristics. The data collection techniques used were document analysis, observation and questionnaires. The research results during the LKPD development process were characterized by project based learning, namely through the define, design and development stages. Initial analysis revealed that class IV A students had never used LKPD, so to overcome this, LKPD was developed which was designed based on the requirements of a good LKPD. The validity of LKPD characterized by project based learning obtained an average of 3.72 with a very valid category. Students' responses to LKPD characterized by project based learning obtained an average of 3.75 in the very good category.